Violence on Philippine Television: An Initial Study on the Frequency and Nature of TV Violence in the Philippines - Foundation, Philippine Children's Television (Review of Women's Studies; Vol 11 No 1-2 (2001): Review of Women's Studies Volume XI, Numbers 1-2 (January-December 2001))
---